Prokaryotic Community Composition and Extracellular Polymeric Substances Affect Soil Microaggregation in Carbonate Containing Semiarid Grasslands - Zethof, Jeroen H. T.; Bettermann, Antje; Vogel, Cordula; Babin, Doreen; Cammeraat, Erik L. H.; Solé-Benet, Albert; Lázaro, Roberto; Luna, Lourdes; Nesme, Joseph; Woche, Susanne K.; Sørensen, Søren J.; Smalla, Kornelia; et al. (Frontiers in Environmental Science, 2020)
In the barren semiarid landscape individual plant species improve soil structure, reducing the erosion risks, whereby microaggregates form the most fundamental soil structural components. Extracellular polymeric substances (EPS) are considered an important glue determining aggregation in addition to inorganic binding agents such as carbonates. However, the role of the prokaryotic community in EPS formation and consequently for microaggregation in natural environments is not substantially clarified yet. EPS should be particularly important under semiarid conditions as it forms a protection mechanism of the prokaryotes against desiccation. Therefore, we examined the influence of the prokaryotic community on soil EPS content and subsequently on soil microaggregation in semiarid grasslands, depending on the parent material, common plant species and the distance to the plant. Soil samples were taken over a distance gradient from two major semiarid grassland plant species in Southern Spain, the legume shrub Anthyllis cytisoides and the grass tussock Macrochloa tenacissima, to the surrounding bare soil at two sites, rich and poor in carbonates. Total community DNA and EPS were extracted, followed by quantification of EPS-saccharide, bacterial abundance and examination of the prokaryotic community composition. Further, the particle size distribution of the microaggregate fraction was determined as an indication of microaggregation. We found that the overall prokaryotic community composition differed between the two sites, but not between plant species. Nonetheless, a link between the community composition and EPS content was established, whereby soil organic matter (OM) seems to be a regulating factor as increasing soil OM contents resulted in more EPS-saccharide. Furthermore, microaggregation was enhanced by the canopy, especially at the edge of Macrochloa tussocks. Contrary to the expectation that increasing inorganic C contents would diminish importance of EPS, the parent material richest in inorganic C resulted in a significant effect of EPS-saccharide contents on microaggregation according to the structural equation model. For the inorganic C poor site, EPS-saccharide had no observed direct effect on microaggregation. Based on our results we conclude that the availability of decomposable OM influences the prokaryotic community composition and thereby triggers EPS production whereas large contents of polyvalent cations promote the stabilizing effect of EPS on microaggregates.